2020
DOI: 10.1002/app.49656
|View full text |Cite
|
Sign up to set email alerts
|

A poly(L‐lactic acid) monofilament with high mechanical properties for application in biodegradable biliary stents

Abstract: In this article, a poly(L‐lactic acid) (PLLA) monofilament with high mechanical properties which can be used to construct biodegradable biliary stents (BBS) is prepared. Compared with a commercial polydioxanone (PDO) suture, the PLLA monofilament has much higher Young's modulus. As a result, chronic outward force (COF) of the stent braided by PLLA monofilament is more than three times higher than that of the stent braided by PDO suture. Furthermore, by physicochemical indexes characterizations, it is acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Such stents have been inserted, e.g., into the esophagus [14,15], intestine [16], bronchus [17], trachea [18] or bile duct [19]. PPDX stents have been widely studied in in vivo medical trials [14,16,[19][20][21][22], their mechanical properties have been investigated [23][24][25][26], and their degradation has also been studied to some extent from a physicochemical point of view [25,27]. Stents made of similar materials have also been analyzed in studies [28] (poly(L-lactic acid) endovascular stent) and [29] (intracoronary stent coated with poly(Llactic acid)).…”
Section: Introductionmentioning
confidence: 99%
“…Such stents have been inserted, e.g., into the esophagus [14,15], intestine [16], bronchus [17], trachea [18] or bile duct [19]. PPDX stents have been widely studied in in vivo medical trials [14,16,[19][20][21][22], their mechanical properties have been investigated [23][24][25][26], and their degradation has also been studied to some extent from a physicochemical point of view [25,27]. Stents made of similar materials have also been analyzed in studies [28] (poly(L-lactic acid) endovascular stent) and [29] (intracoronary stent coated with poly(Llactic acid)).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] To improve the mechanical properties of monofilaments, solid-state drawing (SSD) method is always chosen which is carried out between the glass transition temperature and the melting temperature of PLLA. 19,20 To fabricate the braided stent, stent is first braided on a special mold, and then annealed at 100 C for 1 h. 21 Many studies have shown that shrinkage occurs during unconstrained annealing process for solid-state drawn PLLA monofilaments. 22,23 However, the PLLA monofilaments used for weaving cannot shrink freely since they are taut with constrained ends in the braided stents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PDO braided stents are preferable to treating some slight benign biliary strictures for several months' support. 10 However, due to complexity and diversity of etiologies, some severe benign biliary strictures will last for over half a year. In these backgrounds, PDO braided stents can not always provide enough support and collapse in advance, leading to adverse clinical events.…”
Section: Introductionmentioning
confidence: 99%
“…The PDO suture has low Young's modulus of about 2 GPa and short degradation period of about 6 months, equipping the BBS with limited radial force within half a year. Therefore, PDO braided stents are preferable to treating some slight benign biliary strictures for several months' support 10 . However, due to complexity and diversity of etiologies, some severe benign biliary strictures will last for over half a year.…”
Section: Introductionmentioning
confidence: 99%